Discovery of rotation axis alignments in Milky Way globular clusters - Piatti, Andres Eduardo (2020)
There is an increasing number of recent observational results that show that some globular clusters exhibit internal rotation while they travel along their orbital trajectories around the Milky Way center. Based on these findings, we searched for any relationship between the inclination angles of the globular cluster orbits with respect to the Milky Way plane and those of their rotation. We discovered that the relative inclination, in the sense of inclination of the rotation axis to orbit axis, is a function of the orbit inclination of the globular cluster. Rotation and orbit axes are aligned for an inclination of ∼56◦ , while the rotation axis inclination is far from the orbit inclination between ∼20◦ and −20◦ when the latter increases from 0◦ up to 90◦ . We further investigated the origin of this linear relationship and found no correlation with the semimajor axes and eccentricities of the globular cluster orbits, nor with the internal rotation strength, the globular cluster sizes, actual and tidally disrupted masses, or half-mass relaxation times, among others. The uncovered relationship will affect the development of numerical simulations of the internal rotation of globular clusters, our understanding of the interaction of globular clusters with the gravitational field of the Milky Way, and the observational campaigns made to increase the number of globular clusters with detected internal rotation.